Keadilan Restoratif Implementation of the Concept of Restorative Justice in the Settlement of Misdemeanor Crimes - Yeheskel Wessy (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
Restorative justice is an alternative approach in the criminal justice system that focuses on recovering losses suffered by victims, the responsibility of the perpetrator, and the involvement of the community in solving criminal acts. This approach does not focus on punishment, but on the restoration of relationships damaged by crime and participatory settlement between victims, perpetrators and social communities. The unity of the indigenous peoples of Southwest Maluku Regency adheres to the culture of Kalwedo and Snyoli Lyeta/Niolilieta/Hiolilieta/Siolilieta (coexistence well) as a culture that is also the highest guideline of life and kinship applied in daily life that regulates kinship relations between individuals and between families in the integrity of life as a customary community. This study is an Empirical Juridical Research that explores the issues through conceptual, statutory, and case approaches. Based on these methods, conclusions and recommendations are formulated. The research and analysis employ the framework of the Criminal Justice System, the concept of Restorative Justice, Indigenous Communities, and the Theory of Balance in assessing the implementation of restorative justice in resolving minor offenses. The findings confirm that in every minor criminal offense committed within the indigenous legal community of Southwest Maluku, axiological values namely the customary values of Kalwedo and Snyoli Lyeta/Niolilieta/Hiolilieta/Siolilieta take precedence over national criminal law (material criminal law). These values serve as legal principles to resolve the offense through non-penal means based on the concept of restorative justice, by imposing customary obligations that require the offender to compensate the victim. This form of simple justice, carried out through customary proceedings, aims to halt the formal criminal process, thereby reducing the burden on law enforcement subsystems and minimizing the state’s financial expenditure related to the prosecution and imprisonment of minor offenders.